Perlindungan Hukum Hak Anak atas Pendidikan Inklusif: Tinjauan Yuridis Kebijakan dan Tata Kelola Kelembagaan PAUD - Elistiana Elistiana; Elsa Mayori (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
This study examines the legal protection of children's rights to inclusive education and its implications for the institutional governance of Early Childhood Education (ECE) in Indonesia. A normative juridical method with a descriptive-qualitative library-based approach is used to evaluate the coherence between macro-level child protection regulations and operational standards for school management. The data are entirely secondary, sourced from statutory laws, ministerial regulations, and pertinent scientific literature. The findings reveal a fundamental tension: the constitutional rights of children with special needs to access non-discriminatory ECE are robustly guaranteed by the 1945 Constitution, Law No. 35/2014 on Child Protection, and Law No. 8/2016 on Persons with Disabilities, yet a wide gap persists at the implementation level. This discrepancy arises because derivative ECE governance instruments including accreditation frameworks and curriculum standards still frame inclusion readiness as a voluntary component rather than a binding obligation. Consequently, ECE institutions encounter systemic barriers in human resource management, physical accessibility, and curricular flexibility. The study underscores the urgency of transitioning ECE management toward a Human Rights-Based Approach (HRBA) and recommends that the Ministry of Basic and Secondary Education reform accreditation instruments by embedding inclusive indicators as mandatory prerequisites for institutional feasibility, thereby aligning administrative governance with the fulfillment of children's constitutional rights.